Identification of specific risk factors and predictive analytics for cardio-cerebral arterial stenosis: a comparative study utilizing framingham risk stratification insights - Gege Zhang; Sijie Dong; Fanfan Feng; Weihao Kan; Taozhen Shi; Hongmei Ding; Ruiguo Dong (BMC Neurology)
Abstract Atherosclerotic diseases are systemic, and stroke patients often present with both intracranial artery stenosis (ICAS) and coronary artery stenosis (COAS). This study aimed to investigate the prevalence of ICAS and COAS among ischemic stroke patients across different risk strata and to construct a predictive model for assessing atherosclerosis risk. This retrospective study included patients admitted for ischemic stroke at the Affiliated Hospital of Xuzhou Medical University from December 2020 to December 2021. All patients underwent CTA, with significant stenosis defined as exceeding 50% for both cerebral and coronary arteries.Patients were categorized into low-, moderate-, and high-risk groups on the basis of the Framingham risk scale. A total of 5,816 patients were included, with a mean age of 66.54 years. Dual arterial stenosis was found in 2,258 patients (38.8%), single ICAS in 399 (6.8%), and single COAS in 3,159 (54.3%). The moderate- and high-risk groups had significantly lower risks of single ICAS and COAS. Comparing the differences in risk factors between single arterial stenosis and dual arterial stenosis, the key risk factors included hyperlipidemia, smoking, hypertension, and diabetes, with a model accuracy of 73.61% and an AUC values of 0.8562 for dual stenosis. Significant differences in age, sex, and the risk factors were observed among risk groups. The predictive model demonstrated high accuracy, highlighting the importance of personalized medicine in clinical decision-making.